The permeable screen: Soviet cinema and the fantasy of no limits. (19th December 2018) - Eakin Moss, Anne
Abstract: This essay seeks a revised understanding of the film medium in the formal stylistics of Soviet cinema in the Stalinist 1930s, which, in their direct confrontation of the spectator and their simultaneous striving for immersive illusionism, share a common impulse both with both 3-D blockbuster moviemaking of today, as well as with the immersive desires of virtual reality. An analysis of Sergei Eisenstein's 1947 essay 'On stereocinema' accompanies close analysis of representative works of Socialist Realist cinema from the 1930s, culminating an examination of the immersive and confrontational effects in the almost parodic 1940 film Svetlyy put'/The Radiant Path, directed by Eisenstein's former assistant, Grigory Aleksandrov. I put this historical analysis in dialogue with contemporary issues in film phenomenology and the 'post-medium condition'. Socialist Realist cinema stands to enhance our understanding of both the signifying possibilities of the medium and how it acts upon the spectator.